2021
DOI: 10.1002/vms3.678
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the higher concentrate ratio on the production performance, ruminal fermentation, and morphological structure in male cattle‐yaks

Abstract: Background The present study evaluated the effects of the different concentrate‐to‐forage ratio on the parameters of production, ruminal fermentation, blood biochemical indices, and ruminal epithelial morphological structure of the male cattle‐yaks. Methods Eight male cattle‐yaks (280 ± 10 kg of body weight) were randomly divided into the high concentrate (HighC, 70% concentrate feeds on a dry matter basis) and low concentrate (LowC, 50% concentrate feeds on a dry matter basis) groups. All the animals were reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 47 publications
(79 reference statements)
1
9
1
Order By: Relevance
“…The C80 group had the highest NH 3 -N content among the three groups, which could be explained by the high-concentrate diet producing more rumen microbial protein. In this study, increasing the proportion of dietary concentrate increased the total VFA yield and the yields of propionate, butyrate and isobutyrate, but decreased the amount of acetate and the acetate:propionate ratio, which was essentially consistent with the results of other studies (10,19,20). Our findings confirm that feeding a high-concentrate diet shifted the rumen fermentation pattern of yaks from acetate to propionate.…”
Section: Discussionsupporting
confidence: 92%
“…The C80 group had the highest NH 3 -N content among the three groups, which could be explained by the high-concentrate diet producing more rumen microbial protein. In this study, increasing the proportion of dietary concentrate increased the total VFA yield and the yields of propionate, butyrate and isobutyrate, but decreased the amount of acetate and the acetate:propionate ratio, which was essentially consistent with the results of other studies (10,19,20). Our findings confirm that feeding a high-concentrate diet shifted the rumen fermentation pattern of yaks from acetate to propionate.…”
Section: Discussionsupporting
confidence: 92%
“…The current study results were greater than some previous studies, which could be due to different growing stages of calves, environmental conditions being more suitable, or probably only one feeder feeding experimental calves, which had no fear of calves during feeding. In addition, according to (Desnoyers et al, 2008;Jiang et al, 2022), dry matter intake was greater than the current study, which found between 2.24-2.60 kg/day. Furthermore, CtFCp-50 and CtFCp-ad libitum in the ruminant diet effectively consumed energy intake and growth performance.…”
Section: Animal Growth Performance Characteristics Energy Estimation ...contrasting
confidence: 84%
“…The current study was similarly designed for several researchers who used limited ruminants to conduct experiments by fed concentrate-to-forage or by-product ratios, replacement, or supplementation. Jiang et al (2022) conducted an experimental design with eight male cattle yaks, four heads for each treatment to compare different concentrate-to-forage ratios. According to Gunun et al (2023), feeding concentrate was replaced by yeastfermented cassava peels for 12 goats by designing three groups with four heads in each group.…”
Section: Dietary Treatment and Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Interspecific hybridization can play a central role in the adaptation and evolution of particular species in nature, with heterosis often resulting from the hybridization of genetically distinct animals ( 10 ). In an effort to improve yak production performance, researchers and breeders have sought to combine the excellent productivity of other cattle species with the QTP-adapted traits of yaks, such as cold tolerance, through interspecific hybridization ( 11 ). The resultant cattle-yaks, which are a hybrid of yaks and conventional cattle ( Bos taurus ), possess the high productivity of cattle and the adaptability of yaks to high-altitude conditions ( 12 ).…”
Section: Introductionmentioning
confidence: 99%